No durable impact of COVID-19 measures on the hospital burden of respiratory syncytial virus (France, 2018–2022). Issue 4 (October 2022) - Fourgeaud, Jacques; Toubiana, Julie; Chappuy, Hélène; Delacourt, Christophe; Moulin, Florence; Parize, Perrine; Scemla, Anne; Abid, Hanene; Leruez-Ville, Marianne; Frange, Pierre
Highlights: Extreme public restrictions transiently delayed the RSV circulation in 2020/2021. In 2021/2022, less "extreme" measures did not mitigate the hospital burden of RSV. The recent RSV epidemic had similar seasonality pattern than pre-COVID-19 outbreaks. The 2021/2022 RSV outbreak involved less subjects with complex chronic conditions. New preventive strategies are needed to reduce the hospital burden of RSV.